(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Background: Surgical and burn wound infection are the most common infection in the hospital settings. Objective: The aim of the present study was to see the status of extended spectrum beta-lactamase (ESBL) producing bacteria isolated from patients presented with surgical and burn wound infection. Methodology: This cross-sectional study was conducted in the Department of Microbiology, BSMMU from January to December 2006, at a period of one year. This study was carried out to detect extended spectrum β-lactamase producing Gram negative bacteria rapidly by using a kit containing chromogenic cephalosporin directly from primary culture by comparison with phenotypic confirmatory method. Result: Total 181 samples were collected from patients with wound infections of which 170(93.9%) bacteria were isolated. Among individual samples ESBLs positive strains were highest in surgical wound which was 22(31.42%) and 24(28.24%) isolates respectively. From surgical wound swab ESBL was found 3(42.9%) isolates from Klebsiella species. ESBL producing E. coli was found in 12(35.3%) isolates. Pseudomonas species showed in 2(22.2%) isolates and 1(33.3%) isolate of Acinetobactor species. ESBL positive E. coli was found in 5(45.45%) isolates from burn wound. ESBL positive Proteus species was detected in 11(28.94%) isolates from burn wound. Conclusion: Most common bacteria isolated from the infected surgical and burn wound are E. coli and Proteus species, though Klebsiella species is the most common ESBL producing bacteria isolated from both infected surgical and burn wound. Bangladesh Journal of Infectious Diseases 2018;5(1):21-26